2009
DOI: 10.4103/0970-1591.57904
|View full text |Cite
|
Sign up to set email alerts
|

Contrast induced nephropathy in urology

Abstract: Intravenous contrast agents have a distinct role in urological imaging: to study precise anatomical delineation, vascularity, and to assess the function of the renal unit. Contrast induced nephropathy (CIN) is a known adverse effect of intravenous contrast administration. The literature on incidence, pathophysiology, clinical features, and current preventive strategies available for CIN relevant to urologists was reviewed. A search of the PubMed database was done using the keywords nephropathy and media, preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 84 publications
(82 reference statements)
1
0
0
Order By: Relevance
“…In such a study with adult inpatients, it was demonstrated that a low osmolar iodine-based CM was not a risk factor for CIN in patients with a baseline eGFR >45 mL/min/1.73m 2 ( 18 ). A very similar result with a CIN incidence of 0.6% (1/170) was achieved by a study with patients having an eGFR >40 mL/min/1.73m 2 ( 19 ). Nevertheless, information about hydration and patient status (in- or outpatient) were missing.…”
Section: Discussionsupporting
confidence: 72%
“…In such a study with adult inpatients, it was demonstrated that a low osmolar iodine-based CM was not a risk factor for CIN in patients with a baseline eGFR >45 mL/min/1.73m 2 ( 18 ). A very similar result with a CIN incidence of 0.6% (1/170) was achieved by a study with patients having an eGFR >40 mL/min/1.73m 2 ( 19 ). Nevertheless, information about hydration and patient status (in- or outpatient) were missing.…”
Section: Discussionsupporting
confidence: 72%